(3QSGdI aj eYfi GdLhgQ hGdgjhdj hGdLSes - (3eMeO SYjO Hf Ydj Hf YHO GdbGOQ Hf eMjj GdOjf GdMSfj GdLRGFQj , (B1390 (3gčs ((3YHO GdbGOQ Hf eMeO Hf jYbhHs)
(3ChdgG (B:s
(3HYO GdMeOdI hGdJUdjI (B: (3hHYO CjgG GdGHf GdcQje CYRc Gddg HYR GdWGYI Efc SCdJfj Yf eYfi GdLhgQ hGdgjhdj hGdLSe hPcQJ Cfc bO (B( ) (3GdPGJ hGdLSe ajgG GfG HYhf Gddg hEYGfJg (B( ) (3CLeY dc eG cGf eJaQbG ef cdGe GdCFeI GdCYdGe GdcQGe hCQHW HYVg dJMUjd GdbUO hGdeQGes
(3BNQgG (B:s
(3hCeG GdeQGHWI agj eYGgOI GdYHO dQHg Ydi Pdc Ke HYOgG Jchf GdeQGbHI hHYO Pdc jMGSH GdYHO faSg Ydi eG GTJQWg hYGgO Ydjg aEf hLO faSg bO haJ MeO Gddg hEf hLOgG bO LdJ YbOI GdeTGQWI hfbVJ YbO GdeQGHWI YGbHgG YbGHG jRLQgG Yf GdYhO Edi eKd Pdc Ke YGO Edi GdeTGQWI hGdeQGHWI hMGhd Ydi GdeQGOs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds